Bioprospecting of marine fungi from the High Arctic: A study of high latitude marine fungi from understudied taxa; bioactivity potential, taxonomy and genomics - Hagestad, Ole Christian (UiT The Arctic University of Norway, 2021)
Marine fungi comprise a group of organisms that have been overlooked for a long time. Research interest has increased with the realization of the important ecological role and rich chemistry of marine fungi. Marine fungi have yielded thousands of new natural products the last decade, but many taxa remain unstudied. Marine fungi from the Arctic have not been reported in literature in regard to bioprospecting campaigns and represent a novel source of natural products. The aim of this thesis is to assess the potential of Arctic marine fungi to produce bioactive secondary metabolites by fermentation and genome analysis. This was achieved in three steps. First, fungi were isolated from the Svalbard archipelago. The 20 isolates obtained were characterized based on molecular markers and their antibacterial activity was tested using an agar diffusion assay (Paper 1). Secondly, three distinct marine fungi were whole genome sequenced and characterized. One of the fungi represented a putatively novel species which was circumscribed based on morphology and phylogenetic inference (Paper 2). Finally, a metabolite from one fungus among the 20 obtained around Svalbard was isolated and the bioactivities characterized (Paper 3). In Paper 1, half of the fungal isolates showed activity against pathogenic bacteria and every third isolate represents potentially new species of fungi. Five of these isolates are strictly marine fungi belonging to the order of Lulworthiales. The study showed that the Arctic can yield novel marine fungal diversity that can be utilized in bioprospecting. For Paper 2, three marine fungi were whole genome sequenced and their biosynthetic gene clusters were characterized. Mapping of the biosynthetic gene clusters (BGCs) within the Emericellopsis genome confirmed the detection of the secondary metabolite helvolic acid produced during fermentation. The study revealed numerous unknown biosynthetic gene clusters and a range of carbohydrate active enzymes. Each of the three genomes provides the first genome of ...